Effects of cocoa butter, palm fraction and emulsifier mixtures on the quality parameters of different chocolate formulations - Kumara, Bakti (2003)
The physico-chemical characteristics of cocoa butter (CB) , palm midfraction (PMF) and palm kernel stearin (PKS) in fat-based chocolate formulation in the presence of sorbitan tristearate (STS) have been studied. Triacylglycerols (TAGs), fatty acid methyl esters (FAMEs), thermal behaviour, polymorphic form, solid fat content (SFC), hardness / texture properties, rheological behaviour, microstructure properties, bloom test, and sensory properties were determined to evaluate quality properties of palm-based chocolate. The results show that the addition of STS into fat system could significantly inhibit the polymorphic transformation during temperature transition. It is due to the significant influence in increasing the crystal stability.This study showed that the melting profiles of fat mixtures with the presence of STS were different due to the rapid melting at room temperature (30°C) , so resulting in the softness of chocolate products. Most of CB, PKS and STS mixtures have a strong tendency to produce two distinctive β and β' polymorphs. These results provide strong evidence to indicate incompatibility between those fats, which causes softness in chocolate and confectionery products. By using response surface methodology (RSM), it was found that a ratio of 90CB: I 0PMF:2.5STS was the optimum formulation for the best physical and chemical characteristics of fat system. The concentrations of TAGs of chocolate's fat were changed, causing the polymorphic transformation to take place during storage. However, only the composition of the main TAGs (POP, POS, SOS) significantly influence the type of polymorphic form, whereas fatty acids composition determined the type of TAGs formed. Chocolate containing CB (control) consisted of only β crystals at all times. However, chocolates containing CB and PMF mixtures were found to strive both β' and β during storage period. The existing of two crystal forms (β' + β) and the transition of W into the more stable β crystal had caused bloom formation. STS at 1.25% and 2.5% were found to inhibit effectively bloom formation during storage. The sensory evaluation of palm-based chocolates showed that texture score was significantly affected by both PMF concentration and onset of melt, but STS did not have any significant effect on each sensory attribute.